Kinerja Keuangan Perusahaan Konsumen Primer: Pengaruh Good Corporate Governance, Manajemen Laba, dan Moderasi Ukuran Perusahaan - Ririn Rahmayani; Ela Widasari; Sri Intan Purnama (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine the effects of Good Corporate Governance (GCG), proxied by independent commissioners, audit committees, and managerial ownership, as well as earnings management, on financial performance, with firm size serving as a moderating variable. A causal associative quantitative approach was employed using secondary data obtained from the financial statements of primary consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was selected through purposive sampling, resulting in 130 observations from 26 companies. Data were analyzed using panel data regression and Moderated Regression Analysis (MRA) with EViews 13 software. The findings indicate that independent commissioners do not have a significant effect on corporate financial performance. In contrast, audit committees, managerial ownership, and earnings management have significant effects on financial performance. Furthermore, firm size is found to moderate only the relationship between audit committees and financial performance, while it does not moderate the relationships between independent commissioners, managerial ownership, or earnings management and financial performance. These findings suggest that the effectiveness of internal governance mechanisms and the quality of corporate governance implementation play a crucial role in maintaining the financial performance of primary consumer sector companies amid the economic dynamics of the post-COVID-19 pandemic.